TRAINING RUN 3 X 10 MINUTE CIRCUIT TRAINING AND CONTINUOUS RUNNING 3 X 10 MINUTES CAN INCREASE VO2 MAX KARATEKA DOJO CHAMPION TONDANO - Ellen B. Lomboan; Maisje Afrida Rompas (Porgram Studi Diluar Kampus Utama (PSDKU) Universitas Pattimura Program Studi Pendidikan Jasmani, 2020)
The purpose of this research were: (1) To determine the extent of the influence of the circuit running drills 3 x 10 minutes to increase VO2 max at the karate dojo Champion Tondano. (2) To determine the extent of the influence of continuous running exercises 3 x 10 minutes to increase VO2 max at Karateka Dojo Champion Tondano. (3) To determine the extent of the effect difference between running drills circuit 3 x 10 minutes and run continuously 3 x 10 minutes to increase VO2 max at Karateka Dojo Champion Tondano. The result of research shows that: (1) The influences of the circuit running drills 3 x 10 minutes to increase VO2 max at Karateka Dojo Champion Tondano. (2) There is the influence of continuous running exercises 3 x 10 minutes to increase VO2 max at Karateka Dojo Champion Tondano. (3). There is a difference of influence between circuits running drills 3 x 10 minutes and run continuously 3 x 10 minutes to increase VO2 max at Karateka Dojo Champion Tondano. Conclusion: The obtained value t-score is great 4.214 more thant-table at 2:56 with a significant p value = 0.026 <0.05. Thus, H0 is rejected, which means There is a difference between the effects of circuit training run 3 x 10 minutes and run continuously 3 x 10 minutes to an increase in VO2 max at the karate dojo Champion Tondano.